A Novel Dual Action Tunable Antimicrobial Silver-Containing Biocomposite; XII International Conference on Nanostructured Materials (NANO 2014), July 13-18, 2014 Moscow, Russia - Pryamushko T. S. Tatiana Sergeevna; Ivanova A. A. Anna Aleksandrovna; Loza K. Katerina; Primak O. Oleg; Mattias E. Epple; Surmeneva M. A. Maria Alexandrovna; Mukhametkaliev T. M. Timur Mukhamedrashidovich; Surmenev R. A. Roman Anatolievich (Thin Films and Heterostructures, 2D and 3D Nanofabrication, 2014)
Title screen